2015
DOI: 10.1016/j.jhep.2015.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin effectively inhibits oncogenic NF-κB signaling and restrains stemness features in liver cancer

Abstract: Background & Aims The cancer stem cells (CSCs) have important therapeutic implications for multi-resistant cancers including hepatocellular carcinoma (HCC). Among the key pathways frequently activated in liver CSCs is NF-kB signaling. Methods We evaluated the CSCs-depleting potential of NF-kB inhibition in liver cancer achieved by the IKK inhibitor curcumin, RNAi and specific peptide SN50. The effects on CSCs were assessed by analysis of Side Population (SP), sphere formation and tumorigenicity. Molecular ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
163
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 259 publications
(179 citation statements)
references
References 50 publications
6
163
0
1
Order By: Relevance
“…As a natural compound, it has been proven to be effective with minimal toxicity, which selectively acts on cancer cells over normal cells (5,6). Hitherto, curcumin and its analog have been reported to play an anticancer role in several tumor models, including glioblastoma (7), liver (8), colorectal (9), lung (10), ovarian (11), breast (12) and oral (13) cancer. The underlying mechanisms have been demonstrated to be associated with the inhibition of proliferation, angiogenesis, invasion and metastasis of cancer cells, or apoptosis induction by curcumin (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…As a natural compound, it has been proven to be effective with minimal toxicity, which selectively acts on cancer cells over normal cells (5,6). Hitherto, curcumin and its analog have been reported to play an anticancer role in several tumor models, including glioblastoma (7), liver (8), colorectal (9), lung (10), ovarian (11), breast (12) and oral (13) cancer. The underlying mechanisms have been demonstrated to be associated with the inhibition of proliferation, angiogenesis, invasion and metastasis of cancer cells, or apoptosis induction by curcumin (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…As a natural compound isolated from plants, curcumin has a low toxicity but a remarkable anticancer effect on various malignancies such as lung cancer, liver cancer, and colon cancer [1820]. Apart from that, curcumin is considered to be a repressor of LSCC growth via topical application [9].…”
Section: Discussionmentioning
confidence: 99%
“…Also, a similar HDAC-inhibitory effect is exhibited by other bioactive food constituents, e.g., curcumin, (185) and allyl isothiocyanate (186). Recently, Maequardt et al (187) demonstrated that curcumin treatment induced cell death in HCC, especially in cells with the aggressive progenitor phenotype, and this effect may be attributed to HDAC inhibition.…”
Section: Other Bioactive Food Constituentsmentioning
confidence: 83%